Exposure to Ethics Education and the Perception of Linkage between Organizational Ethical Behavior and Business Outcomes - Luthar, Harsh K.; Karri, Ranjan (Journal of business ethics, 2005)
This study focused on the effects of individual characteristics and exposure to ethics education on perceptions of the linkage between organizational ethical practices and business outcomes. Using a stratified sampling approach, 817 students were randomly selected from a population of approximately 1310 business students in an AACSB accredited college of business. Three hundred and twenty eight of the subjects were freshmen, 380 were seniors, and 109 were working managers and professionals enrolled in a night-time MBA program. Overall, the respondents included 438 male students and 379 female students. Exposure to ethics in the curriculum had a significant impact on student perceptions of what should be the ideal linkages between organizational ethical practices and business outcomes. Gender based differences were found with female students having a higher expectation regarding what should be the "ethics practices and business outcomes" link. Exposure to ethics in the curriculum had a positive moderating influence on the gender-based effects on perceptions of ideal ethical climate. The interaction effect showed that exposure to ethical education may have a positive impact on males and allow them to catch up with females in their ethical sensitivities concerning the ideal linkage between organizational ethical behavior and business outcomes. Further, consistent with the literature, the study found that gender differences in ethical attitudes regarding the ideal ethical climate, while significant for undergraduates, appeared to narrow considerably for the working professionals who were part-time MBA students.